Genome-wide analysis and expression profiling suggest diverse roles of GH3 genes during development and abiotic stress responses in legumes - Singh, Vikash K.; Jain, Mukesh; Garg, Rohini (Frontiers in Plant Science, 2015)
Growth hormone auxin regulates various cellular processes by altering the expression of diverse genes in plants. Among various auxin-responsive genes, GH3 genes maintain endogenous auxin homeostasis by conjugating excess of auxin with amino acids. GH3 genes have been characterized in many plant species, but not in legumes. In the present work, we identified members of GH3 gene family and analyzed their chromosomal distribution, gene structure, gene duplication and phylogenetic analysis in different legumes, including chickpea, soybean, Medicago and Lotus. A comprehensive expression analysis in different vegetative and reproductive tissues/stages revealed that many of GH3 genes were expressed in a tissue-specific manner. Notably, chickpea CaGH3-3, soybean GmGH3-8 and -25, and Lotus LjGH3-4, -5, -9 and -18 genes were up-regulated in root, indicating their putative role in root development. In addition, chickpea CaGH3-1 and -7, and Medicago MtGH3-7, -8, and -9 were found to be highly induced under drought and/or salt stresses, suggesting their role in abiotic stress responses. We also observed the examples of differential expression pattern of duplicated GH3 genes in soybean, indicating their functional diversification. Furthermore, analyses of three-dimensional structures, active site residues and ligand preferences provided molecular insights into function of GH3 genes in legumes. The analysis presented here would help in investigation of precise function of GH3 genes in legumes during development and stress conditions.